STRATEGI PENERJEMAHAN PUISI-PUISI CHAIRIL ANWAR OLEH RAFFEL DALAM BUKU THE COMPLETE PROSE AND POETRY OF CHAIRIL ANWAR - Raja Rachmawati (Balai Bahasa Provinsi Riau, 2013)
This article discusses Indonesian—Poetry translation. The purpose of this article is to describe the strategies of translating poetry of Chairil Anwar by Raffel Raffel in “The Complete Prose and Poetry of Chairil Anwar”, a book written and edited by Raffel Raffel. In order to reach the purpose, the poetries of the source language are compared with the poetries of the target language in order to find out the strategy used in the translation. The method applied in this study is a qualitative descriptive analysis of the meaning. The data were analyzed by using some strategies of translation theory in general given by Newmark, Vinay and Dalberhet, Baker, and Hoed and the strategy of translating poetry by Lavefere. The result of the analysis shows that the general translation strategy used in the translation of Chairil Anwar Poetries are modulation translation, calque or literal translation, descriptive equivalence translation, generic words translation, additional translation and interpretation translation. Meanwhile the strategies of translating poetry used by Raffel are metrical translation, rhymed translation, blank verse translation, and interpretation translation. Penelitian ini membahas penerjemahan puisi bahasa Indonesia kedalam bahasa Inggris. Tujuannya adalah mendeskripsikan strategi penejemahan puisi-puisi Chairil Anwar oleh Raffel Raffel dalam bukunya yang berjudul The Complete Prose and Poetry of Chairil Anwar. Untuk mencapai tujuan penelitian ini, puisi-puisi Chairil Anwar dalam bahasa Indonesia dibandingkan dengan terjemahannya dalam bahasa Inggris. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Data dianalisis dengan menggunakan strategi penerjemahan secara umum yang dikemukakan oleh Newmark, Vinay dan Dalberhet, Baker, and Hoed dan strategi penerjemahan puisi oleh Andre Lavefere. Hasil analisis menunjukkan bahwa strategi penejemahan umum yang digunakan dalam menerjemahkan puisi Chairil Anwar adalah strategi penerjemahan modulasi, calque atau penerjemahan literal, kesepadanan deskriptif, penerjemahan dengan kata generik atau kata yang lebih umum, penerjemahan dengan tambahan dan penerjemahan dengan pengurangan. Sedangkan strategi penerjemahan puisi yang digunakan oleh Raffel adalah penerjemahan metris, penerjemahan rima atau sajak, penerjemahan bait secara bebas, dan penerjemahan interpretasi.